Russian university teachers’ ideas about pedagogic frailty - Svetlana Nikolaevna Kostromina (Knowledge Management & E-Learning: An International Journal, 2017)
The paper focusses on the problem of pedagogic frailty in Higher Education in Russia. The main dimensions of pedagogic frailty are described from the point of view of Russian teachers and researchers. Concept maps were used to reveal the teachers’ ideas about the challenges presented by ‘pedagogic frailty’. The content analysis of their concept maps revealed interviewees’ perceptions of the possible options that can be used to generate solutions to the problems created by pedagogic frailty. The detailed analysis of original solutions and examples observed in the interviewees’ concept maps is presented. Based on the results of the research, guidelines about solutions to the problem created by pedagogical frailty are proposed.